PERLINDUNGAN HUKUM ATAS MEREK TERKENAL TERHADAP PIHAK LAIN YANG MENDAFTARKAN MEREK YANG SAMA ANALISIS PUTUSAN NOMOR:37/PDT.SUS- MEREK/2019/PN.NIAGA.JKT.PST - Muhammad Hadiid (2020)
The brand is a very important part in a product because the brand is a marker between a product and other products. The brand also serves to explain the origin of the product. Protection for brands is given to protect brand owners so that their brands are not recognized by other parties, violations of brands are very common in the trading world, especially on well-known brands. As happened in the case of trademark dispute between DIESEL & its variations and DIESELINDUSTRIE, in that case the DIESELINDUSTRIE brand owned by the defendant has imitated a well- known brand from the country of Italy namely DIESEL & its variations which basically have already been registered in the Directorate General of Intellectual Property (djki). Of course this is already contrary to the provisions of Law No.20 of 2016 concerning brands and geographical indications.